2017
DOI: 10.1038/srep45510
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment in Paget’s disease with invasive ductal carcinoma: an observational study based on SEER

Abstract: The aim is to analyse the clinical presentation, treatment and outcomes in patients with Paget’s disease with invasive ductal carcinoma (PD-IDC), with special emphasis on the role of surgical treatment. Using data obtained by the Surveillance, Epidemiology, and End Results (SEER) program from 2010–2013, we investigated the differences in characteristics, overall survival (OS), and breast cancer-specific mortality (BCSM) between patients with PD-IDC and those with invasive ductal carcinoma (IDC). Compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…After adjusting for other tumor characteristics and treatment approaches, we found that PD alone was not associated with inferior survival both in IDC and DCIS, supporting the consensus that the treatment strategy for MPD should be determined by the underlying breast cancer . Due to the high rate of false‐negative imaging findings and high incidence of multicentric or multifocal in situ and invasive carcinomas, the traditional surgery for PD is mastectomy with or without axillary dissection .…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…After adjusting for other tumor characteristics and treatment approaches, we found that PD alone was not associated with inferior survival both in IDC and DCIS, supporting the consensus that the treatment strategy for MPD should be determined by the underlying breast cancer . Due to the high rate of false‐negative imaging findings and high incidence of multicentric or multifocal in situ and invasive carcinomas, the traditional surgery for PD is mastectomy with or without axillary dissection .…”
Section: Discussionsupporting
confidence: 58%
“…After adjusting for other tumor characteristics and treatment approaches, we found that PD alone was not associated with inferior survival both in IDC and DCIS, 10 supporting the consensus that the treatment strategy for MPD should be determined by the underlying breast cancer. 4,14,21,22 Due to the high rate of false-negative imaging findings and high incidence of multicentric or multifocal in situ and invasive carcinomas, the traditional surgery for PD is mastectomy with or without axillary dissection. 12 In this study, the univariate Cox regression analysis results showed that partial mastectomy was associated with a better prognosis in PD-IDC despite no significant difference in the multivariate analysis, and there was no significant difference between partial mastectomy and mastectomy in the PD-DCIS survival analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, as SEER did not report the type of LN surgery, we used the number of LNs excised as an alternative. We define patients with 1–5 LNs removed as sentinel lymph node biopsy (SLNB) and >5 LNs removed as axillary lymph node dissection (ALND), as previous studies reported 13,14. A total of 6,219 female patients with DCISM met our inclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Paget's disease (PD) of the breast is a very rare presentation of breast malignancy, accounting for 1-3% of all primary breast tumors [1][2][3]. PD of the breast emerge as erythematous and ulcerated nipple.…”
Section: Introductionmentioning
confidence: 99%